Neglecting the black woman’s pain: Using the Social Amplification of Risk Framework to explain the alarmingly high mortality rate of black women in UK healthcare institutions. - Sawyerr, Z.N.A. (2020)
This dissertation analyzes the socioeconomic issue of institutional racism in the UK healthcare system, particularly for black women. Much of the literature surrounding this topic falls under an analysis of the historical roots and backgrounds of a country/economy and a separate and independent analysis of their healthcare systems. This dissertation, however, intends to link these two through an analysis of colonial and post-colonial ideologies hand in hand with the treatment of black women in the UK healthcare system, using the Social Amplification of Risk Framework as a tool. It further assesses the current business and risk management practices of some healthcare organizations and proposes a newer, innovative and more effectual means of business management in the form of Enterprise Risk Management. The overarching outcome of this dissertation is to assert and defend that racism is not a thing of the past and that colonial and post-colonial sentiments are still present in the running’s of key institutions in our global economy. Not only will this body of work analyze and critique, but it will also present a simple model as well as suggestions and best practices for both healthcare organizations and governing bodies to exemplify to achieve racial equality and racial equity in our global economy, particularly in the Global North.